Meningkatkan kemampuan pemecahan masalah matematis dengan model cooperative learning tipe student teams achievement division (STAD) pada siswa SMP - Nurhidayah, Nita; Hutajulu, Masta; Fitrianna, Aflich Yusnita (IKIP Siliwangi, 2024)
The ability to solve problems is an essential skill that students must have in everyday life and as an integral part of the math curriculum. The research aims to achieve and improve the mathematical problem-solving ability of junior high school students through the application of the STAD (Student Teams Achievement Divisions) cooperative learning model. The method used is a quasi-experimental design experiment. The results of the study found that before the implementation of the STAD model, students' mathematical problem-solving skills were still low, as seen from the results of the pre-test. This study concluded that cooperative learning STAD is effective in achieving and improving the mathematical problem-solving ability of junior high school students.